Life Transitions: Overseas Study, Work And Career For Young Singaporeans - Harwood, Aramiha (Penerbit Universiti Sains Malaysia (USM Press), 2008)
The author explores the study, work and career pathways of Singaporean students, coming to Australia to complete a tertiary qualification and returning to Singapore to pursue work and careers. Within these pathways, an attempt is made to understand the complexity of influences which shape their life choices and decisions. The background of Singapore, its social and economic development, and its Asian and western cultural foundations, is placed in the context of young Singaporeans studying in Australia. In relation to youth pathways research, particular dimensions of structure and agency are applied to the experiences of these students. Family and culture, education, (Singapore) state, the workforce economy and globalisation are all identified as structural influences. At the agentic level, role conflict and negotiation, reflexivity risk-analysis and identity are identified. Twenty-four participants in Singapore, self-identified as Singaporean and having studied in an Australian university, took part in a semistructured interview and were asked to reflect on their life stories as study to work pathways. Twelve of the parents of the participants were interviewed, to provide perspectives on their children's pathways. It was found that there is a complex interaction of structure and agency throughout the participants' life stories, taking place on an everyday basis. Attempting to understand this interaction requires an understanding of fundamental concerns in participants' lives at critical junctures of transition from study to work. The concept of identity provides insight into the 'ultimate concerns' of participants, allowing for changes and developments, through the changing affiliations and relationships experienced at different stages of their life stories. The roles and affiliations linked to a changing identity, in the case of these participants moving between countries, cultures and institutions, provides the basis for understanding the relative effects of structure and agency in their study to work transition.